Analisis Peluang Dan Tantangan Ekspor Furnitur Rotan (Studi Kasus Pada Perdagangan Indonesia Dengan Korea Selatan) - Nura Siti Nuraiman; Daspar Daspar (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study examines the competitiveness, opportunities, and challenges of Indonesian rattan furniture exports to the South Korean market. Employing a qualitative descriptive approach supported by SWOT analysis and secondary data from the Central Statistics Agency (BPS), the Ministry of Trade, and Trade Map, the study reveals that export performance peaked at USD 45.2 million in 2021 before declining to USD 23.2 million by 2024. Despite Indonesia's dominant position as the world's primary rattan supplier accounting for approximately 85% of global production structural constraints including limited SME production capacity, inadequate logistics infrastructure, weak importer partnerships, and insufficient digital marketing hinder the full realisation of export potential. The IK-CEPA trade agreement, which eliminates tariffs to 0%, combined with the growing eco-minimalist lifestyle trend among South Korean urban consumers, presents a strategic window of opportunity. The SWOT analysis positions Indonesia in the SO (Strengths–Opportunities) quadrant, necessitating an aggressive market penetration strategy. Key recommendations include strengthening strategic partnerships with Korean importers, leveraging Coupang and Naver Shopping e-commerce platforms, enhancing SME production capacity through financing schemes, and developing a distinct Indonesian rattan brand identity for the premium segment.